2024
DOI: 10.3892/mmr.2024.13217
|View full text |Cite
|
Sign up to set email alerts
|

Long non‑coding RNA DANCR aggravates breast cancer through the miR‑34c/E2F1 feedback loop

Shuai Yan,
Lizhi Teng,
Juntong Du
et al.

Abstract: Emerging scientific evidence has suggested that the long non-coding (lnc)RNA differentiation antagonizing non-protein coding RNA ( DANCR ) serves a significant role in human tumorigenesis and cancer progression; however, the precise mechanism of its function in breast cancer remains to be fully understood. Therefore, the objective of the present study was to manipulate DANCR expression in MCF7 and MDA-MB-231 cells using lentiviral vectors to knock down or overexpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…lncRNAs can be located in the cytoplasm ( 28 ), nucleus ( 29 ), nucleolus ( 30 )s, and other subcellular regions and vesicles (such as nucleoli and exosomes), and their localization is related to their molecular functions ( 28 , 31 ). Certain sequence motifs in their primary sequences are related to subcellular localization ( 32 ).…”
Section: Lncrnas Localization and Related Research Techniquesmentioning
confidence: 99%
“…lncRNAs can be located in the cytoplasm ( 28 ), nucleus ( 29 ), nucleolus ( 30 )s, and other subcellular regions and vesicles (such as nucleoli and exosomes), and their localization is related to their molecular functions ( 28 , 31 ). Certain sequence motifs in their primary sequences are related to subcellular localization ( 32 ).…”
Section: Lncrnas Localization and Related Research Techniquesmentioning
confidence: 99%
“…It has also been reported that roles of DANCR in the carcinogenesis, with an especial emphasis on its role in the development of osteosarcoma and lung, liver, pancreatic and CRC [ 11 ]. Study also showed DANCR may potentially provide a promising future therapeutic strategy for breast cancer treatment [ 12 ]. Previous research has reported that DANCR played a critical role in Doxorubicin-induced apoptosis in colorectal cancer cells through regulating the expression of MALAT1 [ 13 ].…”
Section: Introductionmentioning
confidence: 99%